The role of colours for mosque in enhancing it as a significant landmark in place - Razali, Rati Radiana (2010)
A mosque is an important building in any development and specifically in Malaysia. It may be due to majority of population which is Muslim. To be the centre, the elements of colour play a key role architecturally, creating dynamism to capture attention among the public apart from cooling effect in our high temperature and humidity. In Islamic townships, where mosques stand, there will always be water, trees and wind. The combination of these elements must intertwine with the mosque architecture and colour scheme and to neutralise these elements together, they will always relate to some appropriates colour which can resemblance their presence as most significance landmark in an Islamic city. There are some more factors that important for mosques such as architectural style, scale or size, location etc. but the factors of colours give a sense of uniqueness to the mosques and it does play such important role to enhance it as a significance landmark for a place. From the research of these whole studies of colours and mosques characteristics, we can determine that there is a certain colour which is the most appropriate to apply for a mosque which related on their characteristics itself. This is to ensure the quality of visual effects in a place. The important roles of colours in general and also for mosques in enhancing it as a significant landmark in a place or city shows that the colours is not only to fill in the emptiness or to highlight an object, but also can be used for an object or building to have their own identity and uniqueness to be recognize by others. This is also important in urban design framework as it can make us aware of the colour choices for a building that must suits to our surround natures, environment and cultures of a place to be a significance landmark.